2018
DOI: 10.1007/s00294-018-0900-2
|View full text |Cite
|
Sign up to set email alerts
|

Mating-type switching by homology-directed recombinational repair: a matter of choice

Abstract: In eukaryotes, all DNA transactions happen in the context of chromatin that often takes part in regulatory mechanisms. In particular, chromatin structure can regulate exchanges of DNA occurring through homologous recombination. Few systems have provided as detailed a view on this phenomenon as mating-type switching in yeast. Mating-type switching entails the choice of a template for the gene conversions of the expressed mating-type locus. In the fission yeast Schizosaccharomyces pombe, correct template choice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 91 publications
3
32
0
Order By: Relevance
“…In this procedure, spores, but not vegetative cells, are stained dark by iodine vapors ( 31 ). Because heterochromatin is required for efficient mating-type switching and thus for homothallic mating and sporulation ( 22 , 32 , 33 ), the Δ K mutant epitype with established heterochromatin forms brown colonies similar to wild-type ( h 90 ) strains, while the Δ K mutant epitype lacking heterochromatin forms light mottled colonies like clr4 Δ strains ( 29 , 30 ). We found that in a Δ K mutant lacking both boundaries the dark epitype could not be readily propagated ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this procedure, spores, but not vegetative cells, are stained dark by iodine vapors ( 31 ). Because heterochromatin is required for efficient mating-type switching and thus for homothallic mating and sporulation ( 22 , 32 , 33 ), the Δ K mutant epitype with established heterochromatin forms brown colonies similar to wild-type ( h 90 ) strains, while the Δ K mutant epitype lacking heterochromatin forms light mottled colonies like clr4 Δ strains ( 29 , 30 ). We found that in a Δ K mutant lacking both boundaries the dark epitype could not be readily propagated ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Heterochromatin formation catalyzed by the histone H3K9 methyltransferase Clr4 occurs rapidly within cenH and, in a subsequent step, the heterochromatic state propagates to the rest of the domain with slower kinetics (21). Once established, heterochromatin is maintained in an RNAi-independent manner (20) to control mating-type switching and to silence the mating-type donor loci (22). The aspect of heterochromatin formation or stability that would be affected by IR-L and IR-R is not known.…”
Section: Significancementioning
confidence: 99%
“…In addition to the allele present at the mat1 locus, the mating type of a population of cells is also determined by the ability to switch and the alleles present at the silent mat2-P and mat3-M regions. Wild type h 90 cells can switch information at the mat1 locus and are mixture of M and P cells [120][121][122][123]. A population that has the M allele at the mat1 locus (mat1M) and lost the ability to switch is h -.…”
Section: Mating Type Loci Serve As a Natural Site For Studying Collapmentioning
confidence: 99%
“…The fission yeast S. pombe, like the budding yeast S. cerevisiae (see above), switches mating type during vegetative growth, though they each use different mechanisms [28]. This provides S. pombe with increased mating opportunities with close relatives.…”
Section: Schizosaccharomyces Pombementioning
confidence: 99%